Self-care behaviour and illness perception in older adults with heart failure in outpatient care - Mária (Magyar Gerontológia, 2025)
Heart failure (HF) is a highly prevalent condition among older adults and associated with a high risk of mortality within one year. Self-care (SC) activities improve health outcomes and reduce hospitalisation and mortality rates in patients with HF.